Existence results for an elliptic DirichletI problem - Giuseppina D'Aguì; Giovanni Molica Bisci (Le Matematiche, 2011)
The main purpose of this paper is to present recent existence results for an elliptic eigenvalue Dirichlet problem. Precisely, our method ensures the existence of an exactly determined open interval (possibly unbounded) of positive parameters for which the problem admits infinitely many weak solutions.